Migratory foreign body in the chest - Hana Abebe Gebreselassie; Biniam Gebremedhin Godu; Maru Gama Erge (Elsevier, 2021)
A 12 years old male child presented to our institution 3 days after he sustained a penetrating injury to his left antero-lateral chest by a sewing needle. At presentation, he was stable except having a localized chest pain at the site of the needle. The pertinent finding was on the chest examination in which there was a pinpointed entry wound at the left 4th intercostal space antero-laterally with a localized tenderness. Chest x-ray revealed a radio opaque foreign body. After obtaining chest ultrasound which localized and marked the needle in the anterior chest wall, local exploration of the chest wall was done over the marked area but foreign body was not found. Hence, thoracic cavity was entered through antero-medial thoracotomy with a finding of a sewing needle in the anterior mediastinum with its tip embedded in the pericardium. Needle was removed without any sequel and patient was discharged improved on the second post-operative day.